An Analysis of Directive Speech Act Used by English Teachers - Diahnisa, Tifani; Arianto, Muhammad Affandi (Journal of English Language Teaching, 2025)
The purpose of this research is to find the kinds of functions of directive speech acts used by English teachers and the most frequently used of directive speech acts performed by the English teachers in the classroom. This research use Yule’s theory of directive speech act, there are five kind of functions, command, request, suggestion, invitation, and warning. This research employed descriptive qualitative method. The researcher as the observer, observe the teaching and learning process videos to gain the data. The data is the utterances performed by the two English teachers as the participant of the research. According to research findings, There are 77 data found in total, 40 data of command, 31 data of request, 1 data of suggestion, 4 data of invitation, and 1 data of warning. The first English teacher tend to perform request to the student with a total of 24 utterances found, meanwhile, the most frequently used of directive speech act from the second English teacher is command with 28 data found. Command is the most frequently used of directive speech in this research.